2015
DOI: 10.12688/f1000research.7386.1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age and intracytoplasmic sperm injection outcome in infertile couples at Khartoum, Sudan

Abstract: Background Intracytoplasmic sperm injection (ICSI) was considered as the mainstay of treatment for male infertility. Nowadays, the scope of ICSI has been widened to include other causes of infertility. There are few published data on ICSI in countries with low incomes. Aims A cross-sectional study was conducted at Saad AbuAlla and Banoun Centers, Khartoum, Sudan to investigate outcomes of ICSI and to determine the parameters that might predict pregnancy success rate following ICSI. Methods The study included 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…However, these findings did not match with previous studies that did not found a significant association between maternal age and the oocyte fertilization rate. 36 On the other hand, the present study observed a significant increase in the status of global DNA methylation among the different age groups where the highest level of global DNA methylation (7.43 ng/μl) has been found in the age group >35 years. A positive association has been found between the status of global DNA methylation and maternal age.…”
Section: Discussioncontrasting
confidence: 53%
“…However, these findings did not match with previous studies that did not found a significant association between maternal age and the oocyte fertilization rate. 36 On the other hand, the present study observed a significant increase in the status of global DNA methylation among the different age groups where the highest level of global DNA methylation (7.43 ng/μl) has been found in the age group >35 years. A positive association has been found between the status of global DNA methylation and maternal age.…”
Section: Discussioncontrasting
confidence: 53%
“…Some results were consistent with our findings (16) . Other authors reported that the outcome of IVF (retrieved oocytes number) was highest in women aged less than 30 years with poor quality embryo and lower percentage of pregnancy were observed in older women (11,15,(17)(18)(19) . However, some reports, which exhibited, that there is no correlation between maternal age and pregnancy rate are still present (20) .…”
Section: Discussionmentioning
confidence: 98%
“…These contradictory views on the pattern of thyroid function in PCOS prompted us to conduct the present study, which aimed to evaluate thyroid function and hormonal profile in patients with PCOS. We have previously shown that PCOS was the main cause of female infertility in Sudan [1112]. …”
Section: Introductionmentioning
confidence: 99%